ADSORPTION OF CE(III) METAL IONS USING MAGNETIC-ALGINATE COMPOSITES WITH BORIC ACID CROSSLINKERS - Jessica Septhila, Jehnni
Cerium is a rare earth metal that has many applications, including as a catalyst in the petroleum industry, as an alloying agent for making specialty metals, and as a component in making color television screens. The abundance of cerium metal which is used especially in the industrial sector is quite high, it can produce waste that is harmful to the environment and the health of living things, so it is necessary to separate cerium metal. Adsorption is an effective method for reducing pollutants such as metal ions and wastewater because the process is quite simple, effective, environmentally friendly, and does not produce toxic by-products. In this research, an alginate-based adsorbent with a cross-linked magnetite core has been prepared using boric acid. The synthesized adsorbents were then characterized using Fourier Transform Infrared Spectrophotometry (FTIR), X-Ray Diffraction (XRD), and Scanning Electron Microscopy Energy X-Ray Dispersive Spectroscopy (SEM-EDS). Optimization of the adsorption of Ce(III) ions using an adsorbent was carried out by varying the mass of the adsorbent, pH and contact time. The results showed that the adsorption of Ce(III) metal ions by Fe3O4-Alginate Boric Acid (MAB) adsorbents reached optimum conditions at pH 4 and a contact time of 4 hours. The adsorption of Ce(III) metal ions by MAB followed the pseudo 2nd order kinetic model and the Langmuir isotherm model with a maximum adsorption capacity (qm) of 37.39 mg/g. The study of the thermodynamics of the adsorption of Ce(III) ions shows spontaneous and endothermic adsorption as indicated by the ?G values at 30, 45, and 60? of -35.695, -39.8211, and -43.9473 kJ mol-1, respectively , and ?H and ?S values of 47.653 kJ mol-1 and 275 J K-1 mol-1